Beyond the Activist Ghetto: A Deductive Blockmodelling Approach to Understanding the Relationship between Contact with Environmental Organisations and Public Attitudes and Behaviour. - Saunders, Clare; Büchs, Milena; Papafragkou, Anastasios; Wallbridge, Rebecca; Smith, Graham (Social Movement Studies, 2014)
Current research on the behavioural impacts of social movements tends to focus on their influence on those most intensely involved. Consequently it overlooks the impacts that social movement organisations might have on those outside the activist ghetto. To begin to address this gap in the literature, this article examines the relationship between contact with environmental organisations and public attitudes and behaviour. Monitoring the electricity use of 72 households has facilitated analysis of its association with their environmental attitudes and contact with environmental organisations. Although standard statistical approaches fail to uncover a relationship between contact with environmental organisations and attitudes and behaviour, a deductive blockmodelling approach tells a different story. Low household electricity use is associated with households sharing pro-environmental attitudes and contact with environmental organisations. High energy use is associated with households not sharing any of these; and moderate energy use is associated with a moderate degree of sharing. Our findings reveal the need for systematic studies of environmental movement organisations' impact on the public's pro-environmental behaviours.